Entrepreneurial identity in comparative historical context: the evolution of French and Chinese family businesses - Lihua LI; Xiaolan ZHOU; Zizheng ZHOU (Humanities & Social Sciences Communications)
Abstract This paper explores the evolution of entrepreneurial identities in two prominent family businesses—Moët et Chandon and the Rong family—highlighting their shift from Darwinian to Communitarian and Missionary types under distinct socio-political pressures. Moët et Chandon evolved within post-revolutionary France, aligning capitalist ambition with aristocratic branding, while the Rong family’s identity navigated national crisis in early 20th-century China, fusing industrial nationalism with Confucian values. To better explain these dynamics, the study extends Social Identity Theory by incorporating self-categorization theory, identity fluidity, and cultural additivity. The comparative approach shows that entrepreneurial identity is not merely a product of market forces but a socially constructed process reflecting broader narratives of modernity, morality, and development. The findings offer valuable insights for future research on how family businesses in different regions and industries navigate socio-political challenges, and the role of cultural and social values in identity formation.